2021
DOI: 10.1017/s0022215121001456
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019: changing the future of emergency epistaxis management

Abstract: Background Acute epistaxis can be a life-threatening airway emergency, requiring in-patient admission. The coronavirus disease 2019 pandemic placed significant strain on hospital resources, and management has shifted towards an out-patient-centred approach. Methods A five-month single-centre retrospective study was undertaken of all epistaxis patients managed by the ENT department. A pre-coronavirus disease 2019 pandemic group was managed with pre-existing guidelines, compared to new gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…7 Studies have shown that this more conservative approach remains safe and effective. [7][8][9] Building on this, some have proposed standardized clinical care pathways for managing epistaxis while minimizing transfers, admissions, and ENT consults. [10][11][12] However, no studies yet have characterized the details of ENT consults for epistaxis in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies have shown that this more conservative approach remains safe and effective. [7][8][9] Building on this, some have proposed standardized clinical care pathways for managing epistaxis while minimizing transfers, admissions, and ENT consults. [10][11][12] However, no studies yet have characterized the details of ENT consults for epistaxis in the ED.…”
Section: Introductionmentioning
confidence: 99%